Alicyclobacillus spp.: New Insights on Ecology and Preserving Food Quality through New Approaches - Emanuela Ciuffreda; Antonio Bevilacqua; Milena Sinigaglia; Maria Rosaria Corbo (Microorganisms, 2015)
Alicyclobacillus spp. includes spore-forming and thermo-acidophilic microorganisms, usually recovered from soil, acidic drinks, orchards and equipment from juice producers. The description of the genus is generally based on the presence of ω-fatty acids in the membrane, although some newly described species do not possess them. The genus includes different species and sub-species, but A. acidoterrestris is generally regarded as the most important spoiler for acidic drinks and juices. The main goal of this review is a focus on the ecology of the genus, mainly on the species A. acidoterrestris, with a special emphasis on the different phenotypic properties and genetic traits, along with the correlation among them and with the primary source of isolation. Finally, the last section of the review reports on some alternative approaches to heat treatments (natural compounds and other chemical treatments) to control and/or reduce the contamination of food by Alicyclobacillus.